STUDI PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN KECAMATAN LHOKNGA KABUPATEN ACEH BESAR - Maryati Maryati; Muhammad Isya; Azmeri Azmeri (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Aceh was hit by Tsunami in 2004 and was beginning to rebuild and rise from adversity especially in terms of building construction. But there are many constructed houses during the reconstruction project that does not suit the societal need and uninhabitable. The purpose of this study is to analyze and describe the implemented construction planning process whether it was considering the societal expectations and participation. This study also investigates the societal representation whether it was represented by all society groups and identifies how to optimize the construction planning process. This research uses semi-qualitative and quantitative methods. This study was conducted in Lhoknga sub-district of Aceh Besar Regency, involving 4 (four) villages and 95 respondents. The data was collected using questionnaires and interviews. The used research instruments are questionnaires and interview sheets that have been tested in terms of validity and reliability. The results show the construction planning process in Lhoknga sub-district of Aceh Besar Regency. This study suggested that the planning process in the sub-district level was not carried properly. Society participation in construction planning was low (58.95%).